Design and Validation of an Instrument to Evaluate Teaching Practices and Conceptions Regarding the use of Cultural Video Games in the Classroom (Foro de Educacion, 2025)
Over the last decade, video games have established themselves as teaching resources capable of promoting meaningful cultural learning, critical thinking and digital literacy at different educational levels. However, the effective incorporation of these playful experiences depends to a large extent on teachers' perceptions of their pedagogical value, as well as on how often and how they decide to use them in the classroom. In the absence of rigorous instruments to measure such perceptions and teaching behaviour. This study presents the validation of the Questionnaire on the Use, Definition and Educational Application of Cultural Video Games (QUDEACV-CUDAEVC), in order to provide empirical evidence to guide teacher training and enhance the critical integration of these resources in the curriculum. An expert judgement (n=10) was applied for content validation and an exploratory factor analysis (EFA) was carried out to explore the internal structure, as well as the calculation of reliability using Cronbach's alpha coefficient. The factor analysis led to the readjustment of the instrument and revealed a new structure composed of three factors related to: teacher characteristics, training, resources available to teachers and elements that are interrelated to their teaching practice and professional profile. The validated questionnaire constitutes a useful tool for the analysis of educational practice, analysing the real interactions that take place in the classroom with the cultural video game and providing the academic community with a replicable model that can be adapted to other research projects.